Effects of resistance training on postural control in Parkinson’s disease: a randomized controlled trial - CHEN, Janini; CHIEN, Hsin Fen; FRANCATO, Debora Cristina Valente; BARBOSA, Alessandra Ferreira; SOUZA, Carolina de Oliveira; VOOS, Mariana Callil; GREVE, Julia Maria D'Andréa; BARBOSA, Egberto Reis (Arquivos de Neuro-Psiquiatria, 2021)
Background: Postural instability affects Parkinson’s disease (PD) patients’ postural control right from the early stages of the disease. The benefits of resistance training (RT) for balance and functional capacity have been described in the literature, but few studies have been conducted showing its effects on PD patients’ postural control. Objective: To investigate the effects of a three-month RT intervention on static posturography (SP) measurements and clinical functional balance assessment among PD patients. Methods: Seventy-four patients were randomly assigned to a three-month RT intervention consisting of using weightlifting machines at a gym (gym group) or RT consisting of using free weights and elastic bands (freew group), or to a control group. The participants were evaluated at baseline, three months and six months. We evaluated changes of SP measurements under eyes-open, eyes-closed and dual-task conditions (primary endpoint), along with motor performance and balance effects by means of clinical scales, dynamic posturography and perceptions of quality of life (secondary endpoints). Results: There were no significant interactions in SP measurements among the groups. Unified Parkinson Disease Rating Scale (UPDRS-III) motor scores decreased in both RT groups (p<0.05). Better perceived quality of life for the mobility domain was reported in the gym group while functional balance scores improved in the freew group, which were maintained at the six-month follow-up (p<0.05). Conclusions: This study was not able to detect changes in SP measurements following a three-month RT intervention. Both RT groups of PD patients showed improved motor performance, with positive balance effects in the freew group and better perceived quality of life in the gym group.
Keywords: Resistance Training; Parkinson Disease; Postural Balance; Rehabilitation; Quality of Life